2012
DOI: 10.15835/nbha4017385
|View full text |Cite
|
Sign up to set email alerts
|

Some Fruit Characteristics of Iranian Cornelian Cherries (Cornus mas L.)

Abstract: Although the Cornelian Cherry is widely grown in the north-eastern areas of Iran, it is not recognized as an important fruit crop as are many other fruit species. Large variability has been observed in all morphological and chemical compositions under study. Fruit weight varied from 1.499 to 3.29 g, whereas seed weight ranged from 0.249 to 0.425 g. The average lengths of fruits were between 15.22 and 22.31 mm, and the average widths of them were between 10.26-16.3 mm. The content of ascorbic acid ranged from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 20 publications
6
36
2
1
Order By: Relevance
“…Similarly, the selection BR-135 that had the highest fruit mass, had also the highest fruit flesh ratio ( Table 1). Similar result was reported by Hassanpour et al (2012) for Iranian cornelian cherries. Thus, for selecting cornelian cherry genotypes it is necessary to pay attention to the bigger fruit mass because it is a trait that positively correlated with the fruit flesh ratio (Karadeniz 2000;Bijelić et al 2007).…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similarly, the selection BR-135 that had the highest fruit mass, had also the highest fruit flesh ratio ( Table 1). Similar result was reported by Hassanpour et al (2012) for Iranian cornelian cherries. Thus, for selecting cornelian cherry genotypes it is necessary to pay attention to the bigger fruit mass because it is a trait that positively correlated with the fruit flesh ratio (Karadeniz 2000;Bijelić et al 2007).…”
Section: Introductionsupporting
confidence: 90%
“…Fruit mass results of our selections were found between limits of previous studies (Bijelić et al 2008b;Bijelić et al 2010;Ercisli et al 2011;Hassanpour et al 2012). However, Yilmaz et al (2009) and Bošnjaković et al (2012) reported exceptional high fruit mass for some selections such as 9.17 g for 77-05 genotype in Turkey and 14.55 g for VR-10 genotype in Serbia, respectively.…”
Section: Physical Characteristicssupporting
confidence: 70%
See 2 more Smart Citations
“…Vitamin C content ranged from 220 ml/100 g in S1 genotype, and 325 ml/100 g for H3 genotype. Hassanpour et al (2012), in analyzing the chemical composition of some cornelian cherry fruits in Iran, reported values between 240-360 mg/100 g fresh weight for ascorbic acid content, and the total soluble solids and total acidity were 5-12.5% and 0.43-1.86%, respectively. …”
Section: Resultsmentioning
confidence: 99%